Cognitive Status Predicts Return to Functional Independence After Minor Stroke: A Decision Tree Analysis - Heldner, Mirjam R.; Chalfine, Caroline; Houot, Marion; Umarova, Roza M.; Rosner, Jan; Lippert, Julian; Gallucci, Laura; Leger, Anne; Baronnet, Flore; Samson, Yves; Rosso, Charlotte (Frontiers in Neurology, 2022)
About two-thirds of patients with minor strokes are discharged home. However, those patients may have difficulties to return to their usual living activities. To investigate the factors associated with successful home discharge, our aim was to provide a decision tree (based on clinical data) that could identify if a patient discharged home could return to pre-stroke activities, and to perform an external validation of this decision tree on an independent cohort. Two cohorts of patients with minor strokes gathered from stroke registries at the Hôpital Pitié-Salpêtrière and University Hospital Bern were included in this study (n=105 for the construction cohort coming from France; n=100 for the second cohort coming from Switzerland). The decision tree was built using CART (Classification and Regression Tree) analysis on the construction cohort. It was then applied to the validation cohort. Accuracy, sensitivity, specificity, false positive and false negative rates were reported for both cohorts. In the construction cohort, 60 patients (57%) returned to their usual, pre-stroke level of independence. The CART analysis produced a decision tree with the Montreal Cognitive Assessment (MoCA) as the first decision point, followed by discharge NIHSS score or age and then by the occupational status. The overall prediction accuracy to the favourable outcome was 80% in the construction cohort and reached 72% accuracy in the validation cohort. This decision tree highlighted the role of cognitive function as a crucial factor for patients to return to their usual activities after a minor stroke. The algorithm may help clinicians to tailor planning of patients’ discharge.